Incorporating Student Interests and Project-Based Learning to Promote Engaging and Sustainable Educational Experiences in Indonesia - Maspul, Kurniawan Arif (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah - 1, 2023)
This study presents valuable information for educators in Indonesia who want to build long-term and inspiring learning experiences. Teachers can foster long-term English language competency by adopting sustainable strategies such as immersive language settings, authentic resources, formative evaluation, collaborative learning, and language skill integration. Implementing project-based learning (PBL) alongside curricular requirements, ongoing professional development, student reflection, and community collaborations provides engaging and long-lasting educational experiences. In addition, encouraging student interest in creative writing across the curriculum enhances communication and critical thinking skills. Students are empowered to become responsible global citizens through sustainable cultural and global education in sustainable agriculture. Educators foster involvement and ownership by incorporating student interests into class planning. Educators in Indonesia can create transformative and impactful learning environments that empower students for lifelong success by embracing these concepts.